Degradation of the EBR-CFRP strengthening system applied to reinforced concrete beams exposed to weathering - Dalfré,Gláucia Maria (2021)
Abstract Little is known about the behavior and durability of strengthening systems applied on concrete substrata and the possible loss of performance due to the degradation of the intervening materials by the structure’s natural aging process and exposure of the externally strengthened elements to aggressive environments. In this context, the present work presents an experimental analysis of the behavior of reinforced concrete beams strengthened with Carbon Fiber Reinforced Polymer (CFRP), applied according to the Externally Bonded Reinforcement (EBR) technique, maintained in a laboratory environment (indoor and protected) or exposed to weathering (outdoor exposure). In addition, specimens of the intervenient materials were also molded and exposed to the same environmental conditions as the beams. The results indicate that weather-exposed epoxy adhesives present reductions up to 70% in their mechanical properties after exposure, while the CFRP composite properties remain similar. It was also found that the strengthening system provided 50% and 28% increments in the load-carrying capacity and stiffness of the elements, respectively. However, the tests conducted after 6 months of weathering exposure showed a 10% reduction in the load-carrying capacity of the strengthened elements.